Performance of a maize/cassava intercrop in tilled and notill Senna spectabilis alley cropping on an Ultisol in southern Cameroon - Hauser, S.; Ndi, J.; Hulugalle, N. (2000)
An intercrop of maize and cassava was cultivated for six consecutive years from 1990/91 to 1995/96. This paper reports on crop performance from the fourth to the sixth year in alley cropping with Senna spectabilis and in a no-tree control, with and without tillage. Maize grain yield increased significantly from 1993 to 1994 (P = 0.0032) and from 1994 to 1995 (P = 0.019). Tillage only had a significantly positive effect on maize grain yield in 1993. Alley cropping had no significant effect on maize grain yield in any year. Cassava root yield was neither affected by tillage nor by alley cropping in any year. Neither the cumulative yields over the three years nor the sum of maize grain and cassava root yield were significantly affected by alley cropping or tillage. No significant interactions were found between cropping system and tillage system.